Integration of immune cells in organs-on-chips: a tutorial - Van Os, Lisette; Engelhardt, Britta; Guenat, Olivier T. (Frontiers in Bioengineering and Biotechnology, 2023)
Viral and bacterial infections continue to pose significant challenges for numerous individuals globally. To develop novel therapies to combat infections, more insight into the actions of the human innate and adaptive immune system during infection is necessary. Human in vitro models, such as organs-on-chip (OOC) models, have proven to be a valuable addition to the tissue modeling toolbox. The incorporation of an immune component is needed to bring OOC models to the next level and enable them to mimic complex biological responses. The immune system affects many (patho)physiological processes in the human body, such as those taking place during an infection. This tutorial review introduces the reader to the building blocks of an OOC model of acute infection to investigate recruitment of circulating immune cells into the infected tissue. The multi-step extravasation cascade in vivo is described, followed by an in-depth guide on how to model this process on a chip. Next to chip design, creation of a chemotactic gradient and incorporation of endothelial, epithelial, and immune cells, the review focuses on the hydrogel extracellular matrix (ECM) to accurately model the interstitial space through which extravasated immune cells migrate towards the site of infection. Overall, this tutorial review is a practical guide for developing an OOC model of immune cell migration from the blood into the interstitial space during infection.